2018
DOI: 10.5005/jp-journals-10024-2259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Analog Scale Scores in Pain Assessment during Pulpotomy using Different Injection Materials in Children Aged 6 to 8 and 8 to 10 Years

Abstract: This research will eliminate block injection of lidocaine in children and utilize infiltration of articaine for pulpotomy treatment of mandibular teeth, hence preventing lingual nerve damage and prolonging paresthesia of IAN, lip, and cheek bite due to IAN block anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Alinejhad et al compared the efficacy of articaine infiltration and lidocaine block on the pulp therapy of primary mandibular second molars in children aged 6-8 and 8-10 years. They used the visual analog scale (VAS) to evaluate the pain during pulpotomy and found that it was significantly lower in the articaine group [27]. Varying results are seen due to the different methodologies and treatments compared with those described in this paper.…”
Section: Discussionmentioning
confidence: 93%
“…Alinejhad et al compared the efficacy of articaine infiltration and lidocaine block on the pulp therapy of primary mandibular second molars in children aged 6-8 and 8-10 years. They used the visual analog scale (VAS) to evaluate the pain during pulpotomy and found that it was significantly lower in the articaine group [27]. Varying results are seen due to the different methodologies and treatments compared with those described in this paper.…”
Section: Discussionmentioning
confidence: 93%
“…Three trials were cross-over RCTs ( 13 , 14 , 16 ). Five trials were conducted on exclusively primary teeth ( 11 - 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pulse rate, blood pressure, respiratory rate, and oxygen saturation were higher in the lidocaine group; however, this difference was significant only for pulse rate and respiratory rate. Different results are related to the different methodologies of the two studies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%